PENGARUH FASILITAS KERJA TERHADAP KINERJA PEGAWAI DI KANTOR DESA TEGALPANJANG KABUPATEN GARUT - Wilma Zuarko Adji; Windi Apriliani Ridwan (EKBIS (Ekonomi & Bisnis), 2022)
This study aims to find out how of work facilities, employee performance, work facilities on employee performance, as well as obstacles that arise and the efforts that must be made on work facilities and employee performance. The object of this research is the Village Office of Tegalpanjang Garut Regency. The method used is quantitative methods, data collection techniques using literature study, observation, and questionnaires. The data analysis technique uses the correlation coefficient and the coefficient of determination with a test tool in the form of SPSS Version 26. Based on the results of the study, it was found that the variable X (Work Facilities) and the Y variable (Employee Performance) had a very strong relationship, namely 0.991 (pearson correlation). The coefficient of determination is 0.983 which indicates that the work facilities have an effect of 98.3% on employee performance and the remaining 1.7% is influenced by other factors not examined by the author. The obstacles faced in this study were the filing cabinets experienced a lack of capacity to accommodate documents, the use of work facilities in Tegalpanjang Village became less effective, this was due to the large number of documents that were not stored in their place. Efforts to overcome this, namely the Tegalpanjang Village office can replace filing cabinets with a larger capacity. Conclusion that work facilities have a very strong relationship to employee performance with a very strong level of influence. Keywords : Work Facilities , Employee Performance.